Cowden Syndrome with Cortical Malformation and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at the Institute for Research on Mental Retardation and Brain Aging, Troina, and University of Naples, Italy report a case of Cowden syndrome presenting with unilateral perisylvian dysplasia and with drug resistant focal seizures.